The Spectrum of Malignant Tumours at a Tertiary Care Hospital in Rawalpindi - Khadim, Muhammad Tahir; Parveen, Bushra; Din, Hafeez Ud; Ameer, Amna; Arif, Ayesha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the frequency of malignant tumors seen in our practice and to provide a foundation for building a comprehensive cancer care strategy. Study Design: Cross-sectional study. Place and Duration of Study: Histopathology Department, Armed Forces Institute of Pathology Rawalpindi, Pakistan from 2009 to 2018. Methodology: All malignant tumors reported from 2009-2018 were retrieved from our tumor registry. This data was analyzed for overall frequency gender distribution, age groups and type/site relationship. Present data was also compared with recent and previous such analyses done both nationally and worldwide, in similar settings and demographics. Results: Total 37793 malignant tumors were diagnosed and registered. Out of this, 22077(58.4%) were males and 15716(41.5%) were females. The most common cancer reported was breast (14.3%) followed by urinary bladder (8.7%), oral (6.7%), lymph nodular (5.5%) and prostatic (5.3%). Malignant tumors in pediatric age group (0-14 years) were found to be 3.4%. Most malignancies were reported in 6th decade of life. Conclusion: There was increase in the total number of the malignant tumors during 2009-2018, as compared to the previous 10 years’ data. Male to female ratio was 1.4:1. The five most common sites in male were urinary bladder, prostate, skin, lymph nodes and oral cavity and pharynx. Whereas in females these were breast, skin, oral cavity, female genital organs (ovary) and lymph nodes.